ANALISIS KOMODITAS UNGGULAN SUBSEKTOR TANAMAN PANGAN DI KABUPATEN KUPANG PERIODE 2016-2020 - Taosu, Esli Onselia; Nurwiana, Ida; Siubelan, Yacobus C.W. (Buletin Ilmiah Impas, 2023)
One characteristic of a region is the availability of natural resources, so the development of natural resources becomes a reference for activities in the various sub-sectors of the area concerned. To find out the food crop sub-sector from existing natural resources, an in-depth study of the leading commodities is needed. This research was conducted in Kupang Regency, from September to October 2022. The research objectives were: 1) To find out the leading commodities of the staple food crop sub-sector in Kupang Regency, 2) To find out the growth and competitiveness of staple food crops in the economy in Kupang Regency. This study used a quantitative approach using secondary data from the Central Statistics Agency (BPS) of Kupang Regency for the 2016-2022 period which consisted of production data from 7 Staple Food Crop Commodities namely rice, corn, soybeans, peanuts, green beans, cassava and cassava. jalar in 24 districts. The analytical method used is Dynamic Location Quotient (DLQ) analysis and Shift Share (SSA) analysis. The results of the study show that the leading commodities in Kupang Regency are rice, sweet potatoes and soybeans where these commodities have a progressive growth rate and are competitive. Rice commodity is a commodity that has a progressive growth rate and has good competitiveness in almost all sub-districts in Kupang Regency, Sweet potato commodity itself is a commodity that has a progressive growth rate and good competitiveness because it is supported by sufficient irrigation channels. both in Kupang Regency so that many Sweet Potatoes are cultivated. While the soybean commodity is a commodity that is mostly produced in Kupang Regency because dry land agriculture dominates the area with limited rainfall. For Commodities Corn, Peanuts, Green Beans, Cassava are also the leading Commodities in just a few Districts.